2017
DOI: 10.1136/bjsports-2017-098208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of illness, poor mental health and sleep quality and low energy availability prior to the 2016 Summer Olympic Games

Abstract: All participants reported at least one illness symptom in the previous month. Low energy availability was a leading variable associated with illness in Olympic-class athletes. The estimates duration of symptoms ranged from 2 to 7 days. Factor analyses show the interdependence of various health domains and support multidisciplinary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 31 publications
1
99
0
2
Order By: Relevance
“…Twenty-two studies reporting mental health symptoms and disorders among current elite athletes were included, presenting data (mostly prevalence) most commonly for symptoms of distress, sleep disturbance, anxiety/depression and alcohol misuse (included in online supplementary appendix 4). 12–30 42–44 Among those, 11 studies reported prevalence data on distress symptoms among 3335 male and female elite athletes (age ranging from 16 to 29 years) from team sports (eg, cricket, football, handball, ice hockey, rugby) and combined Olympic sports (eg, boxing, gymnastics, judo, rowing, swimming) 12–14 16 19 21 23 25 42–44. Based on our meta-analysis, we found that 19.6% (95%CI: 16.0 to 23.3) of elite athletes reported symptoms of distress (high between-study heterogeneity: Q=77.1, P<0.001, ^2=85.7%).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Twenty-two studies reporting mental health symptoms and disorders among current elite athletes were included, presenting data (mostly prevalence) most commonly for symptoms of distress, sleep disturbance, anxiety/depression and alcohol misuse (included in online supplementary appendix 4). 12–30 42–44 Among those, 11 studies reported prevalence data on distress symptoms among 3335 male and female elite athletes (age ranging from 16 to 29 years) from team sports (eg, cricket, football, handball, ice hockey, rugby) and combined Olympic sports (eg, boxing, gymnastics, judo, rowing, swimming) 12–14 16 19 21 23 25 42–44. Based on our meta-analysis, we found that 19.6% (95%CI: 16.0 to 23.3) of elite athletes reported symptoms of distress (high between-study heterogeneity: Q=77.1, P<0.001, ^2=85.7%).…”
Section: Resultsmentioning
confidence: 82%
“…The reference check of the included studies resulted in three additional relevant studies 12–14. Consequently, our systematic review includes 34 original studies: 18 including exclusively current elite athletes,12 13 15–30 11 including exclusively former elite athletes31–41 and four including both current and former elite athletes 14 42–44. The PRISMA flow chart of the search procedure is presented as figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding illness, there is strong evidence to suggest that immunodepression can occur as a result of strenuous exercise (Castell et al, 2019;Peake et al, 2017), and a high incidence of upper respiratory tract illness is frequently reported (Drew et al, 2018;Nieman, 1994), before and particularly after endurance events. Low-energy availability has been identified as a key nutritional factor in such illness (Drew et al, 2018;Heikura et al, 2018); however, the provision of nutritional supplements to alleviate exercise-induced immunodepression and to aid more rapid recovery in athletes has also been well studied. Sometimes certain supplements initially appear promising, but further intensive investigation fails to provide sufficient evidence of consistent beneficial effects on some aspects of exercise-induced immunodepression.…”
Section: Therapeutic Nutritional Supplements and Prophylactic Aidsmentioning
confidence: 99%
“…Raysmith and Drew (2016) produced a figure that demonstrated the risk of failure in a variety of international competitions, which was attributed to the weeks of modified training due to illness or injury ( Figure 3). Epidemiological data from international competition events show that 5-21% of elite athletes experience illness episodes, with higher proportions in females and in endurance events (Alonso et al, 2010;Drew et al, 2018;Schwellnus et al, 2016;Timpka et al, 2017). The recorded incidences of URTI in these elite athletes ranged from 18% to 50%, with several studies reporting infection as the most frequent cause.…”
Section: Subclinical and Clinical Illnessmentioning
confidence: 99%